Historical, normative and theoretical foundations of Inspection in the improvement of the quality of teaching - Esteban Frades, Santiago (Avances en Supervisión Educativa, 2026)
The paper offers a systematic reflection on the role of the Inspectorate of Education as a key element in improving the quality of the Spanish educational system. From a historical perspective, it analyzes the evolution of the inspection from the nineteenth century to the present, highlighting its contribution, more or less intense according to the periods, to pedagogical innovation and the consolidation of the school system. It also examines the evolution of the concept of educational quality in the academic field and its progressive incorporation into regulatory frameworks, with special attention to Organic Law 3/2020, of 29 December, which amends Organic Law 2/2006, on Education (LOE), equity, inclusion, the competitive approach and continuous improvement as structural principles of the system. From this framework, it is argued that the current professional, organizational and regulatory configuration of the inspection places this technical body in a strategic position to drive improvement processes, provided that the burden of bureaucratic tasks is reduced and its pedagogical dimension is strengthened. As a final proposal, the educational inspectorate should prioritize its performance on teacher support, since it is an essential variable for the quality of the educational system. Strengthening their teaching function through mentoring and career guidance is a key strategy for improving teaching and, with it, student outcomes
Keywords: Educational Inspectorate; quality of the education system; educational supervision; profession; equity and inclusion; continuous improvement; pedagogical leadership.